Characteristics and Treatment Results of 5 Patients with Fibrous Dysplasia and Review of the Literature. (14th June 2015) - Ozdemir Kutbay, Nilufer; Sarer Yurekli, Banu; Kartal Baykan, Emine; Baydur Sahin, Serap; Saygili, Fusun
Abstract : Aim . Fibrous dysplasia is a rare bone disease caused by missense mutation leading to abnormal fibroblast and osteoblast proliferation and increased bone resorption. FD can present in monostotic or polyostotic forms. About 3% of FD could be in association with McCune-Albright syndrome (MAS). Because FD is a rare disease, there is limited data in the literature about characteristics of disease and response to treatment. Methods . We present our five cases of FD with general properties and their responses to medical treatment. Results . Two of our patients had polyostotic and three had monostotic FD. One of the polyostotic patients had MAS. One of our patients had surgery for femur fractures, facial asymmetry, and findings of compression. Four patients were given pamidronate; one was given zoledronic acid as bisphosphonate treatment. Bone pain was relieved in all patients with medical treatment. Conclusion . There was a decrease in bone turnover markers to some degree with medical treatment but no radiological improvement was observed.